2010
DOI: 10.1080/00268971003649315
|View full text |Cite
|
Sign up to set email alerts
|

PFI-ZEKE photoelectron and high resolution photoionization spectra of ND3with MQDT simulations

Abstract: The rotationally resolved PFI-ZEKE (pulsed-field ionization zero-kinetic energy) photoelectron spectrum of ND 3 has been recorded at the v 2 + = 0, 1 and 2 thresholds, by single-photon VUV excitation from the ground-state. An assignment of the 2 2 A X     1 1 A X  spectrum is presented, allowing a determination of the adiabatic ionization potential of ND 3 (82261.7(15) cm-1) and of the rotational constants and positions of the v 2 + = 0, 1 and 2 vibrational levels of the ND 3 + ion. These parameters are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…[39][40][41] One consequence of symmetry and nuclear spin constraints is that only transitions originating from the lower (+) inversion component of the ground state appear in bands in which the final ߥ ଶ is even, whereas only transitions from the upper (−) inversion 35 component appear in bands with final ߥ ଶ odd. Therefore, two vibrational transitions must be excited to probe all individual rotational states.…”
Section: B Rotational Levels and Initial State Selection Of Ndmentioning
confidence: 99%
See 4 more Smart Citations
“…[39][40][41] One consequence of symmetry and nuclear spin constraints is that only transitions originating from the lower (+) inversion component of the ground state appear in bands in which the final ߥ ଶ is even, whereas only transitions from the upper (−) inversion 35 component appear in bands with final ߥ ଶ odd. Therefore, two vibrational transitions must be excited to probe all individual rotational states.…”
Section: B Rotational Levels and Initial State Selection Of Ndmentioning
confidence: 99%
“…9 Fully deuterated ammonia, ND 3 , has been observed in prestellar cores. 10 Cheung et al 11 noted that the 35 observed NH 3 emission intensities from interstellar sources do not correspond to a single rotational temperature. In addition, the inversion transition was detected for the rotational level j k = 11 9 , 12 which should not be populated at interstellar temperatures of 10-300 K, and the j k = 3 3 inversion transition has been predicted 13 40 and observed 14 to exhibit maser activity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations